Penerapan Algoritma Apriori Untuk Memprediksi Tingkat Kelulusan Mahasiswa (Studi Kasus: Program Studi Manajemen Informatika dan Komputerisasi Akuntansi Universitas Imelda Medan) - Panjaitan, Muhammad Iqbal; Rajagukguk, Denni M; Manalu, Mamed Rofendi; Karo-karo, Siddik; Sihombing, Monang Juanda Tua (Cattleya Darmaya Fortuna, 2023)
Forecasting is an estimate or prediction regarding the occurrence of an event or events in the future or is a study of historical data to find systematic relationships, trends and patterns. This research discusses how to predict or forecast student graduation rates. By utilizing student master data and student graduation data, it is hoped that we can produce information about graduation rates using student master data through Forecasting techniques. The graduation rate category is measured by length of study and GPA. The algorithm used is an a priori algorithm, the information displayed is in the form of support and confidence values ​​for each graduation level category.